Nacho Libre [videorecording (DVD)] - Hess, Jared, 1979-; Hess, Jared, 1979-; Black, Jack, 1969-; Black, Jack, 1969-; Stormare, Peter (Paramount Pictures, 2006)
Ignacio 'Nacho' is a cook by day in a Mexican orphanage who moonlights as a lucha libre wrestler to raise money for the orphans.